Effects of Formaldehyde on Respiratory Mucosa in Rats - Yorgancilar,E (Sociedad Chilena de Anatomía, 2012)
Formaldehyde inhalation, are known to be nasal mucosa irritating feature. This study we are examined the effects histopathologic of formaldehyde inhalation on rats by using light microscopy. 16 adult wistar albino rats were used in this study. 8 rats were in control group and 8 rats were in experiment group. Experiment group was exposed to 10 ppm formaldhyde 8hours/day,5days/week for 8 week. Nasal mucosa was removed and placed in 10% formaline. Sections were stained with Hematoxylene-Eosine and observed under light microscopy. The lining epithelium of respiratory mucosa showed a loss of ciliated cells with metaplasia of goblet cells and hyperplasia of squamous cells.